KORELASI PENGGUNAAN MEDIA, DISIPLIN BELAJAR DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR IPS - Minto Santoso (Center of Language and Cultural Studies, 2015)
The objective of this study is to see relationship between learning media, learning discipline, and learning motivation toward learning achievement. The study used ex post facto design. Sample of this study was the 54 fifth and sixth graders of MI Hidayatul Ulum Dayu Nglegok Blitar. Data were analyzed using linear regression and porcessed using SPSS Windowsn Version 18. The findings of the study are there is linear relationship between: (1) media and learning achievement (.123 or 12.3%), (2) discipline and achievement (.329 or 32.9%), (3) learning motivation and achievement (.644 or 64.4%), and (4) media, discipline, motivation and achievement .833 (83%).